A Topology Optimization Method based on Nastran Card Quickly Modifying Parameter - Chu Chaomei; Xi Chengjie; Tang Haichuan; Miao Guo (Jixie chuandong)
A topology optimization method based on Nastran card quickly modifying parameters is proposed to solve the problem of modifying parameters of the complex components in the process of topology optimization.In the process of the model modification,the load calculation results can be directly imported to the Nastran topology optimization file to replace parameters of the original one. In consequence,the parameters are quickly modified,the accuracy of parameter modification is increased and the process of the model modification is simplified. In order to further verify the adaptability of Nastran cards quickly modifying parameters topological optimization method to the complex components model,one transmission housing is taken as a research object and its gearbox topological optimization model is modified separately by the Nastran cards quickly modifying parameters method and the Optistruct software. The result shows that the results of the two methods are the same in the same initial condition. The application practice indicates that the Nastran cards quickly modifying parameters method is an effective way to solve the problem of modifying parameters of the complex components.